Genética da espiritualidade: análise genética de Médiuns espíritas - Scalia, Luana Araújo Macedo (2017)
Introduction: Religion and spirituality (R / E) are important aspects in the life and culture of a large part of the population. Although religious practices are universal and evidence demonstrates their clinical importance, the biological basis of such behavior is poorly investigated, particularly at genetic levels. Objectives: To verify the association of 5- HTTLPR, SNP polymorphisms in the 3 'UTR region (rs3813034) of the 5-HTT gene, Val66Met of the BDNF gene, and 48 bp repeats on exon III of the DRD4 gene with mediumship and religiosity / spirituality; In addition to verify the relationship between the gene polymorphisms of spiritist mediums and control group and personality traits. Methods: The study included 130 volunteers, 75 Spiritist mediums and 55 non-medium volunteers from the control group. Genotypes of the 5-HTTLPR polymorphisms, rs3813034 SNPs of the 5- HTT gene, Val66Met of the BDNF gene and exons of the exon III of the DRD4 gene were distinguished. The volunteers answered the following questionnaires: P-DUREL, Cloninger’s Temperament and Character Inventory (ITC) and Self-Report screening questionnaire (SRQ). Results: Spiritist mediums scored high religiosity in P-DUREL and high scores on the ITC’s character dimensions compared to the control group. There was no significant difference between SRQ + of mediums (20%) and control group (26.8%). There was no association between genotypes and mediumship or religiosity by P-DUREL. There was an association between the 5-HTTLPR genotypes, the rs3813034 SNP and DRD4 gene repetition and Cloninger's Autotranscendence (AT) subscales. The subscale Transpersonal Identification was exclusively associated with genotypes of spiritist mediums. Conclusion: Spiritist mediums have personality traits associated with good mental health and low prevalence of mental disorders. According to the results, there are indications that 5-HTTLPR and rs3813034 polymorphisms of the 5-HTT gene and the DRD4 can affect the character dimension of self-transcendence of the TCI when mediumship is present.